Forest-wide bird survey at 183 sample sites the Andrews Experimental Forest from 2009-2019 (Reformatted to a Darwin Core Archive) - Sarah J. K. Frey; Hankyu Kim; Matthew G Betts (Environmental Data Initiative, 2021)
This data package is formatted as a Darwin Core Archive (DwC-A, event core). For more information on Darwin Core see https://www.tdwg.org/standards/dwc/. This Level 2 data package was derived from the Level 1 data package found here: https://pasta.lternet.edu/package/metadata/eml/edi/359/2, which was derived from the Level 0 data package found here: https://pasta.lternet.edu/package/metadata/eml/knb-lter-and/4781/3. The abstract below was extracted from the Level 0 data package and is included for context: Bird occurrence data collected at 183 sample locations within the H. J. Andrews Experimental Forest (HJA) from 2009-present. We used a stratified, systematic, random design to select sample locations. We stratified across elevation, distance to road, and habitat type (plantation or mature/old-growth forest). We conduct point counts on six separate occasions from May – July, which corresponded to spring arrival and subsequent breeding period for the majority of bird species at HJA. Surveys occur between 05:15h and 10:30h and each consists of a 10-min point count where we record all birds seen or heard. The species of all birds seen and heard are recorded as well as all individual squirrels, chipmunks and pikas seen and heard. Survey-level information is also collected at each point count and includes: weather and wind conditions, stream noise, snow cover on the ground, phenology of vine maple and rhododendron. Data collection is ongoing. The H.J. Andrews Experimental Forest is a living laboratory that provides unparalleled opportunities for the study of forest and stream ecosystems in the central Cascade Range of Oregon. Since 1980, as a part of the National Science Foundation Long Term Ecological Research (NSF-LTER) program, the Andrews Experimental Forest has become a leader in the analysis of forest and stream ecosystem dynamics. Long-term field experiments and measurement programs have focused on climate dynamics, streamflow, water quality, and vegetation succession. Currently researchers are working to develop concepts and tools needed to predict effects of natural disturbance, land use, and climate change on ecosystem structure, function, and species composition. The Andrews Experimental Forest is administered cooperatively by the USDA Forest Service Pacific Northwest Research Station, Oregon State University and the Willamette National Forest. Funding for the research program comes from the National Science Foundation (NSF), US Forest Service Pacific Northwest Research Station, Oregon State University, and other sources.